1991
DOI: 10.1091/mbc.2.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Distinct modulatory effects of bryostatin 1 and staurosporine on the biosynthesis and expression of the HIV receptor protein (CD4) by T cells.

Abstract: A family of structurally related macrocyclic lactones, bryostatins, have recently been shown to display several intriguing pharmacologic properties. Bryostatins are biosynthetic products of bryozoa phyllum of marine animals. To extend the analyses of the biological activities of these highly unusual biosynthetic animal products, we have examined the effect of bryostatin 1 (bryo-1) on the steadystate expression of the human immunodeficiency virus receptor, CD4, by normal peripheral blood T lymphocytes. Incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Bryostatin, a macrocyclic lactone isolated from endosymbiont γ-proteobacterial Endobugula sertula [42], is an activator of protein kinase C (PKC) and has been shown to have diverse biological activities. Recently, we and others have shown that bryostatin has anti-HIV-1 activity via various mechanisms, such as blocking the effect of stromal-cell-derived factor-1 (SDF-1), which it does by down regulating its CXCR4 receptors [43] or modulating CD4 and CXCR4 receptors [44,45]. Bryostatin is currently being used in a phase I clinical trial in patients with nonhematologic tumors, and in a phase II trial for relapsed multiple myeloma [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Bryostatin, a macrocyclic lactone isolated from endosymbiont γ-proteobacterial Endobugula sertula [42], is an activator of protein kinase C (PKC) and has been shown to have diverse biological activities. Recently, we and others have shown that bryostatin has anti-HIV-1 activity via various mechanisms, such as blocking the effect of stromal-cell-derived factor-1 (SDF-1), which it does by down regulating its CXCR4 receptors [43] or modulating CD4 and CXCR4 receptors [44,45]. Bryostatin is currently being used in a phase I clinical trial in patients with nonhematologic tumors, and in a phase II trial for relapsed multiple myeloma [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…It has been described that bryostatin has anti-HIV-1 activity via various mechanisms, such as blocking the effect of stromal-cell-derived factor-1 (SDF-1), which is performed by down-regulating CXCR4 receptors 21 or modulating CD4 and CXCR4 receptors 22 23 . Bryostatin also causes dephosphorylation of CDK2 which inhibits RNA polymerase-II phosphorylation 24 , thus impairing HIV-1 Tat function 25 .…”
mentioning
confidence: 99%
“…NF‐κB then translocates to the nucleus, where it binds to the HIV LTR and promotes transcriptional activation (). Drugs targeting these pathways, such as tumor necrosis factor‐α, prostratin, and bryostatin, are currently under study for the treatment of latent HIV infection 23 , 24 , 25 . Prostratin, a phorbol ester that targets both the PKC and NF‐κB pathways, activates HIV transcription in several J‐lat cell‐line models of HIV latency 24 .…”
Section: Induction and Clearance Strategies: “Kick And Kill”mentioning
confidence: 99%
“…Bryostatin, a macrocyclic lactone, is another candidate that targets the PKC and NF‐κB pathways. In addition to modulating the PKC and NF‐κB pathways, bryostatin‐1 also downregulates the CD4 receptor on T cells, which limits the ability of HIV to infect these cells () 25 . Importantly, bryostatin does not activate T cells and has low cytotoxicity 27 .…”
Section: Induction and Clearance Strategies: “Kick And Kill”mentioning
confidence: 99%